AN OVERVIEW OF INNOVATION CAPABILITY FOR SUSTAINABLE BUSINESS FUTURE - Ria Satyarini (Universitas Katolik Parahyangan, 2024)
Small and medium enterprises contribute significantly towards Indonesia’s economy, since they are scattered widely throughout rural areas, the create substantial employment opportunity for local people as well as create many various products. While many large businesses had to lose their operation during the pandemic, small and medium enterprises were able to survive in order to create more innovation for the product and their business. The pandemic hit the economy very strongly and SMEs can survive if they can manage the innovation capability. The development of innovation capability started in 2000 and it has been growing until today. Innovation capability innovation capability will be more focused and stronger if it has digital adaptability. The primary goals of this paper are to present the model for development of innovation capability by systematic literature review, to collect the differences and similarities of methods that used in innovation capability research, understand deeply the dimensions of innovation capability, and know the future research in innovation capability. This research uses a systematic literature review method, that used more than 35 journals from Scopus access and another reputation access in 2020. The research funding that an area implementation of innovation capability varies widely with the research methodology the most researcher used is quantitative research. The dimension that construct the variable varies from internal and external dimension and innovation capability can improve and develop by finding the relationship with variables which still observed, cooperation and network is one of interest field to research. The limitation of the research is that the systematic literature review only focuses on journals published in Scopus and only in 2020, although researchers also review some of the best non-Scopus journals in the field of innovation capability.